Witch Hunting in Seventeenth-Century England: a Historiographical Review - Rachael MacLean (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2015)
An explanation of witch hunting in seventeenth-century England must explain two principle facts: the rise in frequency of witch persecution during the late sixteenth and early seventeenth century, and the gender and socioeconomic distribution of those tried for witchcraft. Few arguments have managed to address the true complexity of English witch trials. While most tried witches were poor women, some were wealthy, active members of the community, and a significant minority of tried witches was male. I found current historiographical arguments about seventeenth-century England witch hunting only partially sufficient and not fully comprehensive. The Thomas/Macfarlane model presents too rigid a binary and doesn’t explain the variation of accused witches, the religious model relies too heavily on a rigid distinction between popular and elite culture, and the psychological model does not manage to cover the full diversity of tried witches or the motives of the accuser. Only by considering elements of each theory can one reach a comprehensive picture of witch hunting that addresses all the evidence.